Rishägn : ett möjligt alternativ som beteskydd vid plantering? - Lidwall, Karin (SLU/Southern Swedish Forest Research Centre, 2019)
Browsing damages is an increasing problem in Swedish forests, the same as for other countries in Europe. Oak, one of the noble broadleaved trees in Sweden, is also one of the most browsed tree species. Many red-listed species are associated with forests that consists of noble broadleaved trees and mixed forests with oak, is the most species-rich ecosystem in Sweden. The most common method to regenerate noble broadleaved forests, is to fence the regeneration area with high fences, by galvanized wire mesh and impregnated poles. The disadvantage is that this method needs both maintenance and removal when the regeneration period is over. Since there is a lack of knowledge about how fences should be designed, decisions on which fence to use is mostly founded by empirical experience. Since 2017, it has been a trial in the nature reserve in Herrevadskloster in Scania, to test if it is possible to build a fence to decrease browsing, by using logging residuals. The field-trial consists of four blocks, with three different treatments, branch-pile fence, wire mesh and control and has been inventoried three times. The result of the inventories suggests that it is a difference of browsing damage between the control and the two fencing methods. The difference between two fences is however smaller. To find out if the branch-pile fence can be a practical- as well as economical good alternative to other types of browsing protections, interviews were conducted with people who had experience of different browsing-protections. According the results from the interview, the branch-pile fencing method took the longest to establish and was because of this also most expensive. But since the branch-pile fence doesn´t need any maintenance or removal there is still a chance that it will become a good alternative to other browsing-protection methods in the future.